Numerical study and identification of cooling of heated blocks in pulsating channel flow with a rotating cylinder - Selimefendigil, Fatih; Öztop, Hakan Fehmi (Elsevier France-Editions Scientifiques Medicales Elsevier, 2014)
A numerical study of pulsating channel flow with heated blocks in the presence of an adiabatic rotating cylinder is performed. The governing equations are solved with a finite volume based commercial solver. The effects of pulsating frequency, Reynolds number and cylinder rotation angle on the fluid flow and heat transfer characteristics from the surface of the heated blocks are numerically studied. It is observed that the flow field and heat transfer rate are influenced by the variations of these parameters. Furthermore, nonlinear models are created to identify the dynamics of the heat transfer for each of the surface of the blocks using system identification. (C) 2014 Elsevier Masson SAS. All rights reserved.
Keywords: Pulsating flow; Rotating cylinder; System identification